2020
DOI: 10.32725/jab.2020.011
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical approach to the anti-inflammatory, antioxidant and antiapoptotic potential of beta-carotene as a protective agent against bromobenzene-induced hepatotoxicity in female Wistar albino rats

Abstract: Bromobenzene is a compound which has contributed much in understanding the mechanisms involved in xenobiotic hepatotoxicity induced by drugs and environment pollutants. In the present study, the protective and ameliorative effect of beta-carotene was investigated against bromobenzene-induced hepatotoxicity and compared with silymarin, a standard hepatoprotective reference drug. Beta-carotene (10 mg/kg b.w. p.o.) was administered to the rats for 9 days before intragastric intubation of bromobenzene (10 mmol/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition to that, the results of the current study showed that the group pretreated with BC and then AMK with BC also showed the protective effect of the BC, which showed a significant decrease (p ˂ 0.05) (near the normal) in serum urea and creatinine, and this demonstrates that the pretreatment of BC can give the same protection as that when administered concomitantly. Many studies have been done and pretreated the rats with BC and demonstrated the protective effect of BC by bringing the biochemical markers near normal and also confirmed by the histological results (11,12).…”
Section: Discussionmentioning
confidence: 77%
“…In addition to that, the results of the current study showed that the group pretreated with BC and then AMK with BC also showed the protective effect of the BC, which showed a significant decrease (p ˂ 0.05) (near the normal) in serum urea and creatinine, and this demonstrates that the pretreatment of BC can give the same protection as that when administered concomitantly. Many studies have been done and pretreated the rats with BC and demonstrated the protective effect of BC by bringing the biochemical markers near normal and also confirmed by the histological results (11,12).…”
Section: Discussionmentioning
confidence: 77%
“…The natural agent PBC is shown to reduce oxidative stress in neurons and blood vessels, including retinal tissue [ 18 , 58 , 59 ]. Moreover, the administration of BC is also known to enhance catalase activity to enhance cytoprotective actions [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that spinach extracts and some of their representative phytochemicals (carotenoids and lutein) provide a hepatoprotective effect by boosting the activity of the superoxide dismutase-1 (SOD1), catalase (CAT), and glutathione peroxidase (GPx1) [64][65][66]. However, when two different models-one for LPS-induced cardiac injury and another for doxorubicin-induced cytotoxicity-were treated with a water-soluble antioxidant extracted from spinach leaves (NAO), contradictory effects were found.…”
Section: Discussionmentioning
confidence: 99%